Prilaku Kuat Tekan Beton Self Compacting Concrete Menggunakan Additive Sika Fume - Adnan Adnan; Didit Arfah Tanro (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to determine the effect of adding the additive Sika Fume on the compressive strength of concrete. This research uses a type of quantitative research with experimental methods, namely by carrying out several tests on test objects in the laboratory. The results of this research show that the compressive strength of concrete with the addition of sika fume varies 0%, 3%, 5%, 7% and 8% of the cement weight, so the experimental results show that the average compressive strength at the age of 28 days of concrete has a variation of 0 % of 26.14 Mpa, 3% variation of 25.01 Mpa, 5% variation of 27.08 Mpa, 7% variation of 24.16 Mpa, 8% variation of 23.40 Mpa. The concrete compressive strength variation of 5% with an average of 27.08 Mpa is the variation with the highest compressive strength value and reaches the design compressive strength. Meanwhile, a variation of 8% with an average of 23.40 Mpa is the lowest compressive strength value and does not reach the design compressive strength.